The influence of combined pretreatment with surfactant/ultrasonic and hydrothermal carbonization on fuel properties, pyrolysis and combustion behavior of corn stalk. (January 2019) - Xu, Xiwei; Tu, Ren; Sun, Yan; Wu, Yujian; Jiang, Enchen; Zhen, Jinrong
Graphical abstract: The mechanism of tween combined with HTC. Highlights: Fuel properties, pyrolysis and combustion behavior of hydrochar was investigated. O/C ratio and HHV of CS + H2 SO4  + tween hydrochar are 0.3 and 28.89 MJ/kg. Lignin was separated with cellulose and hemicellulose via HTC combined with surfactant. Tween inhibited formation and adsorption of pseudo-lignin and promoted hydrolysis of CS. E decreased from 271.16 to 21.68 kJ mol −1 via combining surfactant with HTC. Abstract: The surfactant/ultrasonic combined with hydrothermal carbonization (HTC) were performed to investigate the effect on fuel properties, pyrolysis and combustion behavior of hydrochar under different condition. The results showed that the C/H and O/C ratio of corn stalk (CS) + H2 SO4  + tween was 1.1 and 0.29, which were close to coal, and the heat value reached 28.89 MJ/kg. HTC combined with ultrasonic/surfactant realized the complete separation of lignin with cellulose and hemicellulose in CS. Ultrasonic restricted the hydrolysis of lignin under alkaline condition and pseudo-lignin formation under acidic condition. Tween inhibited the formation and deposition of "pseudo-lignin". The thermogravimetric (TG) experiments displayed the tween combined with HTC improved the pyrolysis temperature and decreased activation energy as well as the combustion ignition temperature which showed better pyrolysis and combustion characteristics. The n th -order kinetic mode was fit with the TG datas. The mechanism of tween combined with HTC was also analyzed.